2012
DOI: 10.1089/aid.2011.0312
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Protease and Reverse Transcriptase Genes of HIV for Antiretroviral Drug Resistance in Jamaican Adults

Abstract: This study reports on the drug resistance profiles for HIV-infected adults in Jamaica using genotypic methods. The genetic diversity of HIV-1 found in these patients was also determined using phylogenetic analysis. Epidemiological data were documented for each patient, blood was collected by venous puncture, and plasma was separated and stored. Viral RNA was extracted and analyzed for mutations in the viral genome by the amplification of the protease and reverse transcriptase (Pro-RT) regions using a nested PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…However, it has been shown that ART used in the presence of drug-resistant viruses may increase the risk of HIV-1 mutagenesis which can compromise the efficacy of ARV therapy (18). With the scaling-up of the treatment programmes in Jamaica, the emergence of HIVDR becomes increasingly more apparent (19). Thus, baseline testing should be seen as standard part of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that ART used in the presence of drug-resistant viruses may increase the risk of HIV-1 mutagenesis which can compromise the efficacy of ARV therapy (18). With the scaling-up of the treatment programmes in Jamaica, the emergence of HIVDR becomes increasingly more apparent (19). Thus, baseline testing should be seen as standard part of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The subtype B dominates the HIV-1 epidemic in most Caribbean islands [7], [8], [9], [10], [11], [12], [13], [14], with exception of Cuba where several non-B genetic forms are collectively more prevalent [15], [16], [17], [18], [19], [20]. Genetic evidence suggests that the HIV-1 subtype B was introduced from Central Africa into America through Haiti around the middle 1960s, coinciding with the return of many Haitian professionals who worked in the Democratic Republic of Congo [21].…”
Section: Introductionmentioning
confidence: 99%
“…13 None of the samples had major protease inhibitor mutations, in contrast to findings among a Jamaican heterosexual cohort. 7 The epidemiology survey through which these samples were obtained did not ask respondents to self-report whether they previously received ARV treatment; it is therefore unclear whether the 26% prevalence of drug resistance is acquired, transmitted, or due to both. The M184V mutation readily emerges during suboptimal lamivudine treatment, but reduces the ability of the virus to replicate.…”
Section: Collins-fairclough Et Almentioning
confidence: 99%
“…4 However, scaling up of antiretroviral use necessitates increased surveillance of HIV drug resistance. 4,5 A transmitted drug resistance of 12-29% has been reported for HIV-infected heterosexuals in Jamaica, 6,7 but estimates of drug resistance among the island's MSM is lacking. Integrating the use of ARV drugs in HIV prevention programs for Jamaica's MSM should be considered since HIV prevalence among this risk group has remained high since 1995, despite HIV educational interventions for behavior change.…”
mentioning
confidence: 99%